2021
DOI: 10.1016/j.radphyschem.2021.109455
|View full text |Cite
|
Sign up to set email alerts
|

Radiation damage effects on zinc oxide (ZnO) based semiconductor devices– a review

Abstract: In space, semiconductor devices are vulnerable to various effect of high energy radiation, causing single event upsets (SEUs), damaging or altering the lattice structure of the semiconductor device. The effect of ionizing radiation on metal oxide semiconductor device had been receiving very little attention as most research focus on polycrystalline silicon-based semiconductor. Based on our previous research studies specifically on gamma ra-diation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…The application of high-energy irradiation is promising as it can change the physicochemical properties of the sensing materials. When high-energy beams interact with the sensing material, they can modify the molecular and structural properties of the materials, including the ionization and development of various types of defects such as interstitial atoms and vacancies [ 124 ]. In this manner, irradiation modifies the structure of the sensing material and may therefore alter its detection capability.…”
Section: Irradiated Gas Sensorsmentioning
confidence: 99%
“…The application of high-energy irradiation is promising as it can change the physicochemical properties of the sensing materials. When high-energy beams interact with the sensing material, they can modify the molecular and structural properties of the materials, including the ionization and development of various types of defects such as interstitial atoms and vacancies [ 124 ]. In this manner, irradiation modifies the structure of the sensing material and may therefore alter its detection capability.…”
Section: Irradiated Gas Sensorsmentioning
confidence: 99%
“…Among metal oxide-based semiconductor, ZnO based semiconductor shows promising result due to its broad application. Belonging in the II-VI semiconductor group, ZnO is known for its direct, wide bandgap ranging within 3.1 to 3.37 eV, has high excitation binding energy of 60 meV, with a hexagonal wurtzite crystal structure [4,5]. Outside the Earth's exosphere, flexible space borne electronics are vulnerable to various types of cosmic radiation.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the apparent damage caused by radiation exposure, a number of past studies concluded that metal oxide-based semiconductors show greater radiation threshold than conventional semiconductors, thus highlighting the importance and necessity in replacing current conventional semiconductors [5]. Recently, the effect of gamma radiation on the electrical performance of a heterojunction pairing of ZnO/CuGaO 2 [7] has been studied and shows varying electrical performance with increasing irradiation while still retaining its semiconductor properties and functionality, despite high radiation exposure [7].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc oxide (ZnO) is a wide band-gap (E g = 3.37 eV) semiconductor, which has a wide range of technological applications, making it an extremely popular research topic in recent years [1][2][3][4][5][6][7]. The crystal lattice of the most common ZnO phase belongs to the wurtzite type and is strongly anisotropic [8][9][10], giving origin to its piezoelectric and pyroelectric properties [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%